The De Franceschi Family Collection at the National and University Library in Zagreb (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The aim of this paper is to give the first insight into the valuable book collection of the De Franceschi family and to present years of work on its arrangement in the National and University Library in Zagreb (NSK), where it probably arrived in 1949 and remained unprocessed in storage until the beginning of this century.   Approach/methodology/design. In order to present the development and historical course of the collection, the authors used the historical-descriptive method, using all the works in which the collection and the De Franceschi family are mentioned. Quantitative results on the content, time period and theme of the collection were obtained with the statistical method, and to a lesser extent with the comparative method comparing the De Franceschi collection with similar family collections. Findings. The creation of the collection and its life after World War II has been reconstructed. Processing and research revealed that the collection contains 58 serial and 2,338 monographic publications ranging from the period of 1503 to 1945. Most of the books had been published in the 19th and the first half of the 20th century with history as the predominant theme and were written in Italian. In addition to material characteristics, the bibliophilic aspects of the material are important, such as signatures of the family members and numerous dedications, which make the collection valuable from cultural and historical perspectives.Originality/value. After more than 75 years of the material being stored in NSK repositories, the printed monographic and serial material were processed and offered to all those interested in its use and study in the library. There is still work to be done on arranging the manuscript material so that the collection is complete.
Keywords: De Franceschi collection; De Franceschi family; Istria; literary heritage